Anxiety Sensitivity Moderates the Association Between Father-Child Relationship Security and Fear Transmission - Bilodeau-Houle, Alexe; Bouchard, Valérie; Morand-Beaulieu, Simon; Herringa, Ryan J.; Milad, Mohammed R.; Marin, Marie-France (Frontiers in Psychology, 2020)
Observational fear learning can contribute to the development of fear-related psychopathologies, such as anxiety disorders and post-traumatic stress disorder. Observational fear learning is especially relevant during childhood. Parent-child attachment and anxiety sensitivity modulate fear reactions and fear learning but their impact on observational fear learning has not been investigated. This study examined how these factors contribute to observational fear learning among children. We examined this question among 55 healthy parent-child dyads. Children (8-12 years old) watched a video of their parent undergoing a direct fear conditioning protocol, where one stimulus (CS+Parent) was paired with a shock and one was not (CS-), and a video of a stranger for whom a different stimulus was reinforced (CS+Stranger). Subsequently, all stimuli were presented to children (without shocks) while skin conductance responses were recorded to evaluate fear levels. Our results showed that children more sensitive to anxiety and who had lower father-child relationship security levels exhibited higher skin conductance responses to the CS+Parent. Our data suggest that the father-child relationship security influences vicarious fear transmission in children who are more sensitive to anxiety. This highlights the importance of the father-child relationship security as a potential modulator of children’s vulnerability to fear-related psychopathologies.